LINGUAPRAGMATIC CHARACTERISTICS OF THE RUSSIAN-UKRAINIAN CONFLICT REPRESENTATION IN CHINESE MEDIA - Oleg I. Kalinin; Konstantin N. Mironenko (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The study is devoted to the linguapragmatic characteristics of the special military operation representation in the media discourse of the People’s Republic of China. The material of 230 media texts from the official newspaper of the Communist Party of China, People’s Daily Newspaper, and 150 publications from the entertainment social network Zhihu was analysed. The research method proposed was a critical content analysis conducted by means of a concordancer programme with keyword extraction and thematic segmentation. The study revealed differences in the use of linguistic means of forming the image of Russia and identified the linguapragmatic features of the studied media texts, which consist in the emphasis on the historical and social- and-political context of the foreign policy events description. At the same time, social media texts paid more attention to the history of relations between Russia and Ukraine, while the official media described the political and economic consequences of the military conflict. The study shows the applicability of content analysis to identifying the linguapragmatics that characterises the image of the country by analysing the linguistic representation of social-and-political events and state institutions in media texts. Further research should be done to investigate the image of Russian institutions in the Chinese media in order to identify the formation of the image of Russia in the Chinese media.